Rancang Bangun Alat Cetak Material Komposit Dengan Sistem Tekan - Muhammad Arsyad Suyuti; Arthur H. Razak; Pria Gautama; M. A. Murtadha; D. H. Wahyuningsi; Wiranto Wiranto (Politeknik Negeri Ujung Pandang, 2022)
The use of composite materials is growing rapidly because it’s have several advantages including easy to form, low density, and abundant availability. This matter encourages composites as substitute metals in various products. The purpose of this research is to make a press tool to form composite panel. The research method is carried out through several stages. The first stage, namely the design process by making sketches or drawings of press tools using Autodesk Fusion software. The second stage is the manufacturing process; components that are not standard were made by machining processes as needed refer to drawings design. The third stage, namely the assembly process, combining each component into a mutually supportive form as planned. The last stage is testing the press tool. At this stage the press tools equipment was tested by pressing eceng gondok (Eichhornia crassipes) fiber to become composite panels. Press tools can make composite panels with thicknesses ranging from 3.67 mm until 4.4 mm. The size of the composite panel follows the size of the mold.